2018
DOI: 10.1016/j.ejps.2017.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Regional aerosol deposition in the human airways: The SimInhale benchmark case and a critical assessment of in silico methods

Abstract: Regional deposition effects are important in the pulmonary delivery of drugs intended for the topical treatment of respiratory ailments. They also play a critical role in the systemic delivery of drugs with limited lung bioavailability. In recent years, significant improvements in the quality of pulmonary imaging have taken place, however the resolution of current imaging modalities remains inadequate for quantifying regional deposition. Computational Fluid-Particle Dynamics (CFPD) can fill this gap by providi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(51 citation statements)
references
References 62 publications
2
49
0
Order By: Relevance
“…A notable signature of the flow is the formation of a laryngeal jet in the presence of the larynx constriction; a feature previously discussed [ 40 , 83 ]. Numerical simulations have shown that the larynx is an important anatomical element that influences aerosol deposition outcomes [ 84 ]: flow acceleration due to the constriction coupled with directional changes due to anatomy contribute to enhanced aerosol deposition near the larynx [ 83 ]. Here, the laryngeal jet is observed across all age points at PIFR, with a peak velocity magnitude reaching a local maximum in the vicinity of the larynx contraction.…”
Section: Resultsmentioning
confidence: 96%
“…A notable signature of the flow is the formation of a laryngeal jet in the presence of the larynx constriction; a feature previously discussed [ 40 , 83 ]. Numerical simulations have shown that the larynx is an important anatomical element that influences aerosol deposition outcomes [ 84 ]: flow acceleration due to the constriction coupled with directional changes due to anatomy contribute to enhanced aerosol deposition near the larynx [ 83 ]. Here, the laryngeal jet is observed across all age points at PIFR, with a peak velocity magnitude reaching a local maximum in the vicinity of the larynx contraction.…”
Section: Resultsmentioning
confidence: 96%
“…Airflow into the IVTT was modelled as a laminar round jet [47], and a Lagrangian particletracking algorithm adopted to compute the droplet trajectories [48]. The forces acting on the droplets were taken to be drag and gravity, which are the dominant forces for aerosol particles in the micrometre range [49]. The change in droplet size and temperature resulting from evaporation of water to the surrounding air was also taken into account, based on previous modelling approaches for soluble aerosol particles [50,51].…”
Section: Modelling Droplet Trajectories In the Ivttmentioning
confidence: 99%
“…These can be described using two non-dimensional particle numbers, namely the Stokes and gravity numbers [10]. We note that a detailed discussion of ensuing air flow patterns in the modeled respiratory tract is omitted here for brevity; flow topologies qualitatively resemble extensive works on the topic [39, 40]. However, for an intubated patient the abrupt diameter change from the tip of the intubation tube to the trachea (Fig.…”
Section: Resultsmentioning
confidence: 99%